PROSPEK USAHA AGROFORESTRY KARET DAN JERNANG DI KABUPATEN SAROLANGUN-JAMBI (Prospects of Rubber and Jernang Agroforestry in the District of Sarolangun- Jambi) - Ardi, Ardi; Kartodihardjo, Hariadi; Darusman, Dudung; Nugroho, Bramasto (SOROT, 2011)
The research was aims to formulate the feasibility of cultivation in combination ofrubber with jernang and minimum area that must be cultivated to meet the needs of decentliving for the community. Research located in Lamban Sigatal village at the DistrictSarolangun in Jambi. Method used is survey method by using questionnaire. The resultobtained, based on calculation of the IRR obtained a value of 16.30% with and interest rateof 15% this illustrates that the cultivation of rubber and jernang agroforestry worthconducting. In order to meet the needs of decent living for farmers, the cultivation of rubberand jernang agroforestry should at least cultivated area of 1.28 hectares.